Application of Constrained Robust Independent Component Analysis in the Fault Diagnosis of Rolling Element Bearing - Liao Qiang; Li Xunbo; Huang Bo (Jixie chuandong)
The method of independent component analysis is widely used in mechanical equipment fault diagnosis domain.A novel method named as constrained robust independent component analysis（ cRobust ICA）based on Robust ICA algorithm is proposed which utilized prior information about the fault characteristic frequency.Firstly,how to create the reference signal is discussed.Then,the measurement function between reference signal and desired independent component（ IC） is defined.At last,an enhanced contrast function is acquired by modifying a generally used kurtosis contrast function with closeness measurement.A contrastive study on the conventional Fast ICA is adopted to demonstrate the effectiveness and accuracy of the cRobust ICA by numerical simulations and experiments.